2009
DOI: 10.1002/dmrr.964
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and endothelin‐1 mediated increased extracellular matrix protein production and cardiomyocyte hypertrophy in diabetic heart disease

Abstract: These data indicate that in diabetes increased FN production and cardiomyocyte hypertrophy may be mediated through leptin with its interaction with ET-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 43 publications
3
33
0
Order By: Relevance
“…The bladder weight and the thickness of the bladder wall were immediately increased at 2 h post-CYP injection and continued increasing until 48 h as examined. There are several possible mechanisms and pathways involved in visceral organ hypertrophy, including increases in the production of extracellular matrix (13,39,40) and increases in muscular growth (13,41). In the current study, we examined the expression level of type I collagen, the main constituent of the extracellular matrix, in the inflamed bladder and found that the mRNA level of type I collagen was significantly increased at 2 and 8 h post-CYP injection and was back to normal level at 48 h post-CYP injection.…”
Section: Discussionmentioning
confidence: 99%
“…The bladder weight and the thickness of the bladder wall were immediately increased at 2 h post-CYP injection and continued increasing until 48 h as examined. There are several possible mechanisms and pathways involved in visceral organ hypertrophy, including increases in the production of extracellular matrix (13,39,40) and increases in muscular growth (13,41). In the current study, we examined the expression level of type I collagen, the main constituent of the extracellular matrix, in the inflamed bladder and found that the mRNA level of type I collagen was significantly increased at 2 and 8 h post-CYP injection and was back to normal level at 48 h post-CYP injection.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies suggest that leptin is an important mediator of pathological cardiac remodeling [13,14,17,19,[21][22][23][24], which is characterized by cardiomyocyte hypertrophy and a disruption of the ECM resulting in increased collagen deposition [1,3]. Here we investigated the effect of leptin on regulation of myocardial matrix components, specifically MMP-2 activity, TIMP-1 expression and collagen-I/-III expression, in HL-1 cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors have been reported to contribute to hyperglycemia-induced cardiac damage, such as oxidative stress (3)(4)(5)(6), mitochondrial dysfunction (5)(6)(7)(8), apoptosis (5-9) and activation of several signaling molecules, including mitogen-activated protein kinase (MAPK) (3,5,10,11), leptin (6,12) and p53 (7,9). Another signaling molecule involved in hyperglycemia-induced cardiomyocyte damage may be nuclear factor-κB (NF-κB).…”
Section: Introductionmentioning
confidence: 99%